Identity matters - Kosic, Marianna (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2012)
The article explores how Slovene minority adolescents in Italy experience and respond to ethnic identity threats, focusing on their coping strategies. These include the active construction of self-image through plural complex identity, seeking and maintaining distinctiveness, blending in and identity enhancement. Qualitative thematic analysis was performed on 35 written narratives, studied through the interpretative lens of social identity perspectives and identity process theory. Results are consistent with the theoretical framework. In the conclusions the author reflects on some practical implications of her findings.
Keywords: Italija; Italy; zamejski Slovenci; slovenska manjšina; mladostniki; narodna identiteta; identitetni motivi